Pre-Columbian Foodways Interdisciplinary Approaches to Food, Culture, and Markets in Ancient Mesoamerica - Staller, John.; Carrasco, Michael; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The significance of food and feasting to Pre-Columbian Mesoamerican cultures has been extensively studied by archaeologists, anthropologists and art historians. Foodways studies have been critical to our understanding of early agriculture, political economies, and the domestication and management of plants and animals. Scholars from diverse fields have explored the symbolic complexity of food and its preparation, as well as the social importance of feasting in contemporary and historical societies. This book unites these disciplinary perspectives $1 (Bfrom the social and biological sciences to art history and epigraphy $1 (Bcreating a work comprehensive in scope, which reveals our increasing understanding of the various roles of foods and cuisines in Mesoamerican cultures. . The volume is organized thematically into three sections. Part 1 gives an overview of food and feasting practices as well as ancient economies in Mesoamerica. Part 2 details ethnographic, epigraphic and isotopic evidence of these practices. Finally, Part 3 presents the metaphoric value of food in Mesoamerican symbolism, ritual, and mythology. The resulting volume provides a thorough, interdisciplinary resource for understanding, food, feasting, and cultural practices in Mesoamerica.s
Ethnography, Ethnobotany, Language and Diet -- An Epigraphic Analysis of Classic-Period Maya Foodstuffs -- Sweet Cacao and Sour Atole: Mixed Drinks on Classic Maya Ceramic Vases -- Prehistoric Chronology of the Common Bean in the New World: The Linguistic Evidence -- Death and Chocolate: The Significance of Cacao Offerings in Ancient Maya Tombs and Caches at Copan, Honduras -- Feasting with Foam: Ceremonial Drinks of Cacao, Maize, and Pataxte Cacao -- Corn, Colanders, and Cooking: Early Maize Processing in the Maya Lowlands and Its Implications -- Potographies and Biographies: The Role of Food in Ritual and Identity as Seen Through Life Histories of Selected Maya Pots and People -- Dietary Diversity in the Upper Belize River Valley: A Zooarchaeological and Isotopic Perspective -- Power Plants: Paleobotanical Evidence of Rural Feasting in Late Classic Belize -- Food and Feasting in the Zona Maya of Quintana Roo -- All Maize Is Not Equal: Maize Variety Choices and Mayan Foodways in Rural Yucatan, Mexico -- Maya Foodways: A Reflection of Gender and Ideology -- Food as Metaphor: Mythology and Iconography -- The Axolotl as Food and Symbol in the Basin of Mexico, from 1200 BC to today -- Topophilia: A Tool for the Demarcation of Cultural Microregions: The Case of the Huaxteca -- This World and Beyond: Food Practices and the Social Order in Mayan Religion -- Maize Was Their Flesh: Ritual Feasting in the Maya Highlands -- From Field to Hearth: An Earthly Interpretation of Maya and Other Mesoamerican Creation Myths -- The Flesh of God: Cosmology, Food, and the Origins of Political Power in Ancient Southeastern Mesoamerica -- Agriculture and Social Complexity: The Roles of Feasting and Ritual Economies -- Pre-Columbian Foodways in Mesoamerica -- Ethnohistoric Sources on Foodways, Feasts, and Festivals in Mesoamerica -- Development of Agriculture in Prehistoric Mesoamerica: The Linguistic Evidence -- The Pastoral Niche in Pre-Hispanic Mesoamerica -- The Drink Mescal: Its Origin and Ritual Uses -- Forming Mesoamerican Taste: Cacao Consumption in Formative Period Contexts -- Salt Production and Trade in Ancient Mesoamerica -- The Dirt on Food: Ancient Feasts and Markets Among the Lowland Maya.
Keywords: Social sciences; Regional planning; Archaeology; Social Sciences; Archaeology; Regional and Cultural Studies